Kernohan-Woltman Notch Phenomenon—Case Report - Pereira, Carlos Umberto (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
The Kernohan-Woltman notch phenomenon is a paradoxical neurological manifestation consisting of a motor deficit ipsilateral to a primary brain injury. It has been observed in patients with brain tumors and with supratentorial hematomas. It is considered a false localizing neurological sign. Magnetic resonance imaging (MRI) scan has been the test of choice. The recognition of this phenomenon is important to prevent a surgical procedure on the opposite side of the lesion. The present case report describes a case of chronic subdural hematoma with a probable finding of the Kernohan-Woltman phenomenon, and it discusses its pathophysiology, imaging findings, treatment, and prognosis.
Keywords: cerebral peduncle; head injury; Kernohan-Woltman notch phenomenon; transtentorial herniation